Una aproximación a la concientización de la importancia del lenguaje como vehículo mediador en los negocios internacionales. (2020)
The following monograph will provide a brief literary review of the relevance of language and communication in international negotiations. This will be done in the first instance with the objective of demonstrating how language contributes to international business, as well as understanding the problems and complications that exist due to the use of a lingua franca in international business today. Therefore, we will investigate through the voice and experience of different experts such as Karl Marx, Sigmund Freud, Ferdinand de Saussure, Rebecca Piekkari and Mary Yoko and from these we will understand how the semiotics, interpretation and different meanings of language affect business communication. The importance of the role that English plays in doing business will also be presented when it is used in the following ways; English as a lingua franca (ELF) and English as a lingua franca in business (BELF). However, from the previous investigations carried out, a series of conclusions and results could be reached, where the result was that whoever handles several languages in an intercultural communicator can carry out different negotiations thanks to his ability to handle different languages in the same way as he does with his native language. It has been found that treating language separately from business and culture can impede effective communication for successful business.